2001
DOI: 10.1038/sj.cgt.7700319
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin chemotherapy plus adenoviral p53 gene therapy in EBV-positive and -negative nasopharyngeal carcinoma

Abstract: We have previously shown that the introduction of human recombinant wild -type p53 mediated by an adenoviral vector ( Ad5CMV -p53 ), either alone or delivered in combination with ionizing radiation, was cytotoxic to two nasopharyngeal carcinoma ( NPC ) cell lines. To further explore the potential therapeutic role for gene therapy, the combination of Ad5CMV -p53 and cisplatin was examined in two NPC cell lines, CNE -1 and C666 -1. The C666 -1 cells are particularly relevant because they express Epstein -Barr vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Consistent with previous studies that show the gene transfer of wild-type p53 as effectively cytotoxic in NPC cells, 18,[21][22][23] our results demonstrated that Ad-p53/GM-CSF/B7-1 infection significantly inhibited cell growth and increased apoptosis of CNE-1 cells in vitro. HuPBL-NOD/SCID mice treated with Ad-p53/GM-CSF/B7-1 demonstrated a reduced tumor burden by 34%-71%, compared with NS groups (p Ͻ 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies that show the gene transfer of wild-type p53 as effectively cytotoxic in NPC cells, 18,[21][22][23] our results demonstrated that Ad-p53/GM-CSF/B7-1 infection significantly inhibited cell growth and increased apoptosis of CNE-1 cells in vitro. HuPBL-NOD/SCID mice treated with Ad-p53/GM-CSF/B7-1 demonstrated a reduced tumor burden by 34%-71%, compared with NS groups (p Ͻ 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…18,[21][22][23] The earliest study noted that a wildtype p53-transfected CNE-3 cell line demon-600 NOD/SCID, nonobese/diabetic severe combined immunodeficiency; NS, normal saline; GM-CSF, granulocyte-macrophage colony-stimulating factors. strated a delay in tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C666-1 cells, an NPC line, were maintained in RPMI medium supplemented with 10% FBS and penicillinstreptomycin and were grown on plates treated with fibronectin (Sigma). C666-1 cells (a gift from Dolly Huang) contain a deletion at codon 249 of p53 (64). 293 cells were maintained in Dulbecco's modified Eagle's medium supplemented with 10% FBS and penicillin-streptomycin.…”
Section: Ebv Cell Linesmentioning
confidence: 99%
“…Weinrib et al . [47] suggested that rAd-p53 and cisplatin interact in an additive manner to kill C666-1 and CNE-1 cells. Somatic cell DNA damage inflicted by chemotherapy does not increase the risk of adenovirus DNA integration into genome.…”
Section: Discussionmentioning
confidence: 99%